Nondestructive evaluation of 3D microstructure evolution in strontium titanate. Issue 2 (21st February 2020) - Trenkle, A.; Syha, M.; Rheinheimer, W.; Callahan, P.G.; Nguyen, L.; Ludwig, W.; Lenthe, W.; Echlin, M. P.; Pollock, T. M.; Weygand, D.; De Graef, M.; Hoffmann, M. J.; et al.
Abstract : X‐ray diffraction contrast tomography is used to investigate the crystallographic, topological and morphological characteristics of the evolving microstructure in thermally aged strontium titanate samples. The analysis of the 3D structure shows a clear signature of the grain boundary anisotropy, which can be correlated to surface energy anisotropy: the grain boundary orientation distribution function shows an excess of ⟨100⟩‐oriented interfaces with respect to a random structure. Abstract : Nondestructive X‐ray diffraction contrast tomography imaging was used to characterize the microstructure evolution in a polycrystalline bulk strontium titanate specimen. Simultaneous acquisition of diffraction and absorption information allows for the reconstruction of shape and orientation of more than 800 grains in the specimen as well as porosity. Three‐dimensional microstructure reconstructions of two coarsening states of the same specimen are presented alongside a detailed exploration of the crystallographic, topological and morphological characteristics of the evolving microstructure. The overall analysis of the 3D structure shows a clear signature of the grain boundary anisotropy, which can be correlated to surface energy anisotropy: the grain boundary plane distribution function shows an excess of ⟨100⟩‐oriented interfaces with respect to a random structure. The results are discussed in the context of interface property anisotropy effects.